Disentangling Rheumatoid Arthritis Patients’ Implicit and Explicit Attitudes toward Methotrexate - Linn, Annemiek J.; Vandeberg, Lisa; Wennekers, Annemarie M.; Vervloet, Marcia; van Dijk, Liset; van den Bemt, Bart J. F. (Frontiers in Pharmacology, 2016)
Medication non-adherence is a major public health problem that has been termed an ‘invisible epidemic’. Non-adherence is not only associated with negative clinical consequences but can also result in substantial healthcare costs. Up to know, effective adherence interventions are scarce and a more comprehensive model of adherence determinants is required to target the determinants for not taking the medication as prescribed. Current approaches only included explicit attitudes such as self-reported evaluations of medication as determinants, neglecting the role of associative processes that shape implicit attitudes. Implicit processes can predict daily behavior more accurately than explicit attitudes. Our aim is to assess explicit and implicit attitudes towards medication and explore the relation with beliefs, adherence and clinical (laboratory) outcomes in chronically ill patients. 52 Rheumatic Arthritis (RA) patients’ attitudes towards Methotrexate (MTX) were explicitly (self-reported) and implicitly (Single-Category Implicit Association Test) assessed and related to the Beliefs about Medicine Questionnaire, the Compliance Questionnaire on Rheumatology and laboratory parameters (Erythrocyte Sedimentation Rate (ESR), C-Reactive Protein (CRP)). Results show that explicit attitudes were positive and health-related. Implicit attitudes were however negative and sickness-related. Half of the patients displayed explicitly positive but implicitly negative attitudes. Explicit attitudes were positively related to ESR. A positive relationship between implicit attitudes and disease duration was observed. In this study, we have obtained evidence suggesting that the measurement of implicit attitudes and associations provides different information than explicit, self-reported attitudes toward medication. Since patients’ implicit attitudes deviated from explicit attitudes, we can conclude that the relationship between implicit attitudes and medication adherence is worthwhile to be further explored. With this information we can improve our understanding of the subconscious, automatic processes underlying adherence and we can develop interventions that target these implicit attitudes.